Legitimitaẗ und Legitimitaẗssicherung von Betriebs- und Personalrat in organisationalen Veran̈derungen - Eine qualitative Analyse; Legitimacy and Legitimacy Preservation of Workplace Employee Representations in Organizational Change - A Qualitative Analysis - Stefanie Faupel; Stefan Sus̈s; Ines Catharina Wulf (Industrielle Beziehungen, 2019)
Die Anzahl organisationaler Veran̈derungen hat in den letzten Jahren erheblich zugenommen. Sie stellen die betriebliche Interessenvertretung vor neue Herausforderungen. An welchen organisationalen Veran̈derungen Interessenvertretungen beteiligt sind und wie sich dies auf die von Beschaf̈tigten zugeschriebene Legitimitaẗ sowie Maßnahmen der Legitimitaẗssicherung auswirkt ist bislang jedoch unklar. Zur Reduzierung des Forschungsdefizits wurden 25 Interviews mit Betriebs- und Personalratsmitgliedern in verschiedenen organisationalen Veran̈derungen gefuḧrt und inhaltsanalytisch ausgewertet. Es zeigt sich, dass sich die Legitimitaẗswahrnehmung abhan̈gig von der Phase der Veran̈derung und ihrer Reichweite unterscheidet. Insbesondere fur̈ die befragten Betriebsratsmitglieder spielt Legitimitaẗssicherung in Veran̈derungsprozessen bislang eine eher untergeordnete Rolle. Dennoch legen die vorliegenden Studienergebnisse den Befund nahe, dass Legitimitaẗ in Veran̈derungssituationen durch die Interessenvertretung beeinflussbar ist. – – The degree of organizational change has increased significantly in recent years. These changes pose new challenges for employee representation at the workplace. However, the role played by workplace employee representation in processes of organizational change and the way this impacts the legitimacy attributed by employees to their representatives as well as actions undertaken by representatives to preserve such legitimacy still remain unclear. In order to address this research deficit, 25 interviews with works council and employee committee delegates faced by organizational change were conducted and evaluated using a content analysis method. The data shows that the perception of legitimacy varies depending on the phase and scope of change. In particular, the interviewed works councilors suggest the preservation of legitimacy plays a minor role during periods of change. Nevertheless, the present study highlights that changes in legitimacy are possible via actions undertaken by workplace employee representatives.
Keywords: J50; J5; M10; M12; M14; 330; organisationaler Wandel; Legitimitaẗ; Legitimitaẗssicherung; Arbeitnehmervertretung; qualitative Interviewstudie; organizational change; legitimacy; legitimacy preservation; workplace employee representation; qualitative interview study